Estratégias de coping no ajustamento familiar de crianças hospitalizadas por Covid-19 e de suas cuidadoras primárias - Bárbara Radieddine Guimarães (2022)
Introduction: Children's hospitalization is a stressful experience for the child and the family. It becomes a unique process when hospitalization is determined by illness from a pandemic disease, such as COVID-19. Although it is an unknown context and apparently influenced by the individual and collective experiences of the pandemic by COVID-19, considering other situations of illness, families seek strategies that allow them to thrive even in adversity. Therefore, it is assumed that coping strategies are adopted by children and their caregivers in order to adjust to the stressful situation. Objective: To analyze the Coping strategies of children and primary caregivers in the family adjustment in the situation of hospitalization for COVID-19. Methodology: This is an exploratory qualitative study, in which McCubbing, McCubbing's (1993) model of stress resilience and adjustment was used. Ten children who were hospitalized for COVID-19 in Belo Horizonte - MG, and fifteen primary caregivers who had their children hospitalized for COVID-19 participated. The data collection was performed by video call, from a questionnaire to obtain sociodemographic information applied to the primary caregivers and two semi-structured interview scripts used for the primary caregivers and another one for the children. The qualitative data were analyzed from the reflective thematic analysis as proposed by Braun and Clark (2016), with support from the MAXQDA© software. Regulatory guidelines and standards for research involving human subjects as per resolutions 466/12 and 510/2016 were met. Results: Primary caregivers who reported greater complicity with the team and prevention strategies against Coronavirus, had predominantly positive appreciations and tended to seek support from professionals. Those who did not perceive this support had predominantly negative evaluations and reported coping strategies related to spirituality and religiosity, loving their children, questioning and/or denying the need for hospitalization of their children, the search for support from family members and friends through conversations by electronic devices and change of companion, when possible. Three children-primary caregiver’s binomials did not agree in their assessments, and only one child reported a predominantly positive assessment. She listed playing and the use of electronic devices as coping strategies. The other children, reported higher intensity of fear, sadness, boredom and longing, used electronic devices to play and talk to their families, spend time with their companions and play. Conclusion: The way children and their primary caregivers live and enjoy the moment of hospitalization is linked to the coping strategies used by them. Health professionals, are fundamental to identify the Coping strategies used by children and their families, favoring their incorporation and supporting them in a more positive family adjustment in this situation of illness.